Morbidity and cost burden of prenatal myelomeningocele repair. (19th May 2021) - Riddle, Stefanie; Huddle, Robert; Lim, Foong-Yen; Stevenson, Charles; Dean, Kristin; Sparling, Karen; Fenchel, Matthew; Schibler, Kurt
Abstract: Objective: This study compared the morbidities and financial burden associated with prenatal open myelomeningocele repair versus postnatal repair. Materials and Methods: The retrospective study cohort included 23 mother-infant dyads undergoing prenatal repair and 30 with postnatal repair. Financial, demographic, and medical information were obtained for mother-infant dyads from each infant's birth through the first year of life. Results: Infants in the prenatal repair group were significantly affected by sequelae of prematurity, including apnea, bronchopulmonary dysplasia, and retinopathy of prematurity. Importantly, fewer of these infants required ventriculoperitoneal shunt procedures and the overall improved composite outcome of shunting or death. Infants in the postnatal repair group required more hospital readmissions in the first year of life. Financial costs for mother–infant dyads in the prenatal repair group were higher, driven by the length of stay in the neonatal intensive care unit and maternal hospital admissions. Kaplan–Meier curves analyzing the relative contributions of the length of stay and total charges in the population were constructed. The maternal contribution was markedly different between groups due to postoperative hospitalization, readmission, and close fetal surveillance required. Though these differences did not reach statistical significance, it highlights an important burden on families and the medical system. Conclusions: This is the first study to report the contributions of prematurity in relation to maternal and infant morbidity and financial costs. The benefits of prenatal myelomeningocele repair include lower risk for ventriculoperitoneal shunting and fewer hospital readmissions. The risk of preterm birth and its neonatal sequelae continue to be a significant burden.